2021
DOI: 10.1108/jd-12-2020-0217
|View full text |Cite
|
Sign up to set email alerts
|

Information behavior during the Covid-19 crisis in German-speaking countries

Abstract: PurposeThe purpose of this study is to explore the impact of the Covid-19 crisis at the level of individual information behavior among citizens from the German-speaking countries, Austria, Germany and Switzerland.Design/methodology/approachAn online survey was conducted among 308 participants gathered through convenience sampling in April and May 2020, focusing on how citizens changed their mix and usage intensity of information sources and according to which criteria they chose them during the Covid-19 crisis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 44 publications
0
36
2
3
Order By: Relevance
“…Retailers can implement corporate citizenship campaigns thus reducing the consumers’ fear of COVID-19and hence its negative effects such as panic buying (Arachchi et al, 2022 ). Meanwhile, COVID-19 crisis could have increased the demand for reliable information alongside a significant use of data provided by public organizations (Dreisiebner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Retailers can implement corporate citizenship campaigns thus reducing the consumers’ fear of COVID-19and hence its negative effects such as panic buying (Arachchi et al, 2022 ). Meanwhile, COVID-19 crisis could have increased the demand for reliable information alongside a significant use of data provided by public organizations (Dreisiebner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…eine zielgruppenspezifischere Kommunikation bevorzugen). FAQ eignen sich zudem insbesondere für Menschen, die sich selbst aktiv informieren [ 58 – 60 ]. Somit ist es wichtig, die FAQ in eine Kommunikationsstrategie zu integrieren, die sich auf mehrere Kanäle und unterschiedliche Instrumente erstreckt und sowohl Zielgruppen selbst als auch Multiplikatorinnen und Multiplikatoren anspricht, um eine möglichst hohe Reichweite zu erzielen [ 20 ].…”
Section: Diskussionunclassified
“…Other studies demonstrated a link between news consumption in general (i.e., not only on social media) and information overload. For example, a study conducted in German‐speaking countries in the first months of the pandemic showed an increase in the demand for reliable information and in the use of public broadcasting, newspapers, and information from public organizations (Dreisiebner et al, 2021). However, the sheer volume and publishing frequency of Covid information during the peak of the crisis led some participants to feel a sense of information overload after intense news consumption, which eventually led to reduced consumption (Dreisiebner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study conducted in German‐speaking countries in the first months of the pandemic showed an increase in the demand for reliable information and in the use of public broadcasting, newspapers, and information from public organizations (Dreisiebner et al, 2021). However, the sheer volume and publishing frequency of Covid information during the peak of the crisis led some participants to feel a sense of information overload after intense news consumption, which eventually led to reduced consumption (Dreisiebner et al, 2021). High levels of Covid news consumption during the first months of the pandemic also led to greater emotional distress (Stainback et al, 2020), and heightened anxiety in parents due to concerns over their children becoming infected (Ebrahim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation